Endurance : Speaking Kurdish in a Warped World - Pillen, Alex, (Brill Kurdish Studies ;, 2024)
In Endurance , Alex Pillen portrays a sense of being unique within Kurdish cultural spheres. How to feel unique despite devastating violence, cultural oppression and assimilation is a question faced by many communities globally. Northern Kurdish (Kurmanji) is a focal point for such uniqueness. When a culture is under siege and many have lost a former way of life it may not be clear how a society looks itself in the mirror, finds its reflection. Alex Pillen's portrayal of Speaking Kurdish in a Warped World locates such lines of reflection within everyday language. The fear of a random geopolitical pair of dice is global, a fear to be honed when reading this account of uniqueness in the face of totalising loss